A proposition of analysis of the effects of different channels performance metrics on market share under economic fluctuations in an emerging market - Rodrigues, Jonny Mateus (2019)
This study aimed to analyze how retail distribution (weighted distribution and numeric distribution) influence market share in emerging markets, depending on different retail formats, heterogeneous regions and economic fluctuations. These markets are increasingly complex, with diversity of channels and players, lack of infrastructure and resources, and sensitivity to economic cycles, which generates concerns about endogeneity. For this purpose, a quantitative and descriptive research was conducted based in two studies. The data were collected from retail audits in Brazil and included in the first study 91 manufacturers, 195 brands, and 1,110 stock-keeping units (SKUs) in soft drinks category, covering in the second study, 343 brands through grocery stores (i.e., self-service and full-service) in seven distinct categories (i.e., beer, cookies and biscuits, laundry detergent, powder coffee, yogurts, shampoo, and ready-to-drink juice) across three different regions in Brazil (i.e., northeast, southeast, and south). First, the results also showed that the effects of numeric (ND) versus weighted distribution (PCV) on market share vary with region and channel format. Although PCV is still a relevant distribution measure, ND becomes important in emerging markets. Findings also suggested that the degree of convexity of market share in retail distribution changes during economic contraction and expansion. The degree of convexity is lower when the economy deteriorates. Thus, brands that are available through stores that represent a high share of the total category\'s sales become less important to sustain market share gains. Furthermore, results indicated the importance of non-weighted measures, such as numeric distribution during tough economic times in an emerging market, whereas, weighted distribution (i.e., PCV) becomes more important as the economy expands. Therefore, it is necessary for marketing managers to understand the interplay between distribution-market share under economic fluctuations, and different retail formats and regions.